COVID-19 and delivery of difficult asthma services. Issue 3 (2nd November 2021) - Nichols, Anna-Louise; Sonnappa-Naik, Mayank; Gardner, Laura; Richardson, Charlotte; Orr, Natalie; Jamalzadeh, Angela; Moore-Crouch, Rachel; Makhecha, Sukeshi; Wells, Charlotte; Hall, Pippa; Bush, Andrew; Fleming, Louise; et al.
Abstract : The COVID-19 pandemic necessitated an urgent reconfiguration of our difficult asthma (DA) service. We rapidly switched to virtual clinics and rolled out home spirometry based on clinical need. From March to August 2020, 110 patients with DA (68% virtually) were seen in clinic, compared with March–August 2019 when 88 patients were seen face-to-face. There was DA clinic cancellation/non-attendance (16% vs 43%; p<0.0003). In patients with home spirometers, acute hospital admissions (6 vs 26; p<0.01) from March to August 2020 were significantly lower compared with the same period in 2019. There was no difference in the number of courses of oral corticosteroids or antibiotics prescribed (47 vs 53; p=0.81). From April to August 2020, 50 patients with DA performed 253 home spirometry measurements, of which 39 demonstrated >20% decrease in forced expiratory volume in 1 s, resulting in new action plans in 87% of these episodes. In our DA cohort, we demonstrate better attendance rates at virtual multidisciplinary team consultations and reduced hospital admission rates when augmented with home spirometry monitoring.